Measurement of Slope Stability on Stone Mines Around Pengsong Hills, West Lombok Area - Zuhdi, Muhammad; Busyairi, Ahmad (Balai Publikasi Indonesia, 2022)
The slope stability angle of the surface landslide stability depends on the friction coefficient between the rock particles in the area. Measurement of slope stability is very useful for the safety of miners in mining areas. Measurement of slope stability is based on the friction coefficient. Measurements are made with a friction coefficient measuring instrument that has been designed and tested. Rock samples were taken at 3 rock mines around Mount Pengsong in West Lombok Regency. The measurement of the friction coefficient was carried out at the Physics Laboratory of the University of Mataram. The measurement results of the friction coefficient are then converted into slope stability angles. The results show that the slope stability angle in the mountains around the rock quarry around Mount Pengsong has a maximum value 5,71 degree of dry sample and 81,0 degree of moisture sample.